IS PUTTING USERS FIRST AN ORGANISATIONAL KEY TO SUCCESS IN CROSS-PROFESSIONAL COOPERATION? An interview study about cooperation between service units to people affected by both intellectual disability and mental illness - Bachke, Carl Christian; Melby, Kristian Leonard; Nilsen, Geir Sigmund (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Cooperation among professionals in health, social and educational sectors is much needed to let the patient/client/pupil experience an entirety of services provided. However, cooperation is not easy in general. It seems even more challenging when it comes to service provisions to people affected by dual diagnoses. Our research question is influenced by this challenge and reads: What promotes cross-units’ cooperation between professionals involved in service provisions for people affected by both intellectual disability and mental illness? The knowledge is constructed by means of interviewing municipality-employed professionals (N = 21) about their experiences with successful cases. The study shows that many aspects contribute to satisfactory cooperation, but three substantial findings are particularly emphasized: (1) Prioritizing user-focus; (2) The management and the organizational structure should be firm, target-explicit and predictable, but at the same time flexible in its use of resources; and (3) Both leaders and staff should show supportive attitudes.